Scaly Leg in Backyard Reared Chicken and its Successful Management - Digraskar, S.U.; Borikar, S.T.; Tawheed, A.S.; Narladkar, B.W.; Nithin, B.S.; Ajabe, J.S.; Shaik , S.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Scaly leg mite (Knemidocoptesmutans) is a small mite, belonging to Sarcoptes group, which usually inhabitat underneath the scales of legs. Knemidocoptesmutans can also infest any unfeathered parts including the face, beak, ears, eyes, combs and wattles of the poultry. The scaly condition if untreated may worsen to very painful condition, loss of toes and even death. Earlier Shastri et al.(1990) reported the infection in backyard poultry birds from Parbhani region. The reports on scaly leg condition in backyard chicken are scanty. The present paper puts on record of scaly leg condition in a local (desi) backyard chicken and its successful therapy.